On Wage-Inequalities in the North and in the South - LEUNG, Hing-Man (Institutional Knowledge at Singapore Management University, 1998)
Northern, developed, skilled-labour rich countries have, in recent years, faced increasing competition from Southern, developing, unskilled-labour rich countries. Many have blamed the South for aggravating the wage-inequality in the North. We build a hybrid model with Heckscher-Ohlin and Ricardian characteristics to tackle this issue. Relative demand for the skilled-labour-intensive good (e.g. cars, computers and computer software) plays a bigger role here than elsewhere in the literature. We find the usual H-O mechanism leads to relative wage convergence, divergence or reversal depending on the relative strength of relative demand, technology and endowment effects. More provocative results arise from innovation/imitation considerations: Northern innovation aggravates Northern wage-inequality but alleviates Southern wage-inequality; Southern imitation alleviates Northern wage-inequality but aggravates Southern wage-inequality.